The role of crop production in the forest landscape restoration approach: Assessing the potential benefits of meeting the Bonn Challenge - De Pinto, Alessandro; Cenacchi, Nicola; Robertson, Richard D.; Kwon, Ho-Young; Thomas, Timothy S.; Koo, Jawoo; Begeladze, Salome; Kumar, Chetan (Frontiers Media, 2020)
Existing approaches and methodologies that investigate effects of land degradation on food security vary greatly. Although a relatively rich body of literature that investigates localized experiences, geophysical, and socioeconomic drivers of land degradation, and the costs and benefits of avoiding land degradation already exists, less rigorously explored are the global effects of restoring degraded landscapes for the health of the land, the climate, and world food security. The current scale of land degradation is such that the problem can be meaningfully addressed only if local successes are upscaled and a large number of landowners and land managers implement restoration activities. Significant global efforts to address degradation exist, but studies that evaluate the global benefits of these efforts generally do not account for global market forces and the complex web of relationships that determine the effects of wide-scale restoration on production and food security. This paper provides important insights into how a full integration of crop production in restoration efforts could impact food production levels, food availability, forest carbon stocks, and Greenhouse gas emissions.